Pelaksanaan dan Faktor yang Mempengaruhi Kepemilikan Surat Izin Praktik Apoteker (SIPA) oleh Tenaga Apoteker di Rumah Sakit dan Puskesmas Kota Surabaya Tahun 2016 - Alvin Faizah (Universitas Airlangga, 2017)
Surabaya had more than 1.600 pharmacists in 2016. However, based on the data there were 144 pharmacists that did not have practice licenses in hospitals and primary health care in Surabaya. It meant that the implementation of The Regulation of Health Minister Number 889 Year 2011 was ineffective. The purpose of this research was describing the pratice lincesing of pharmacist in hospitals and primary health care in Surabaya and the factors that influenced the problem. This research was an observational descriptive study with cross sectional method. Primary data were collected through observation, interview and discussion with the staff in charged in Surabaya Public Health Office. While the secondary data could be achieved from official documents, reports, and archives. Comparing the number of pharmacists in the hospitals or primary health care with the minimum manpower standard of pharmacist based on The Regulation of Health Minister Number 56 Year 2014, the result showed that 33 hospitals had not fulfilled the standard minimum number of pharmacists which mean they had not made their practice licenses. Therefore, the given recommendation was strengthening Public Health Office’s role to direct warning and punishment toward hospitals and pharmacists.Keywords: pharmacist, practice license, hospital and primary health care